Analysis Of The Form Of Working On Make-Up, Clothing, And Properties Of The Lilin Shiva Dance In Palembang City - Rully Rochayati; Muhammad Jazuli; Hartono Hartono; Wahyu Lestari (International Conference on Science, Education, and Technology, 2023)
The purpose of this study was to examine the role of make-up, clothing and dance properties in Lilin Shiva dance in the city of Palembang. The Lilin Shiva dance is an important part of Palembang culture, and has a rich history and cultural significance. This study will investigate how makeup, clothing, and dance props are used to enhance the beauty and grace of the Lilin Shiva dance, and how they contribute to the overall performance. Qualitative research methods will be used, and data will be collected through observation and interviews with artists, choreographers and make-up artists. It is hoped that the findings of this study will provide insight into how makeup, clothing, and dance props can be used to enhance traditional dance forms, while staying true to their cultural roots. This research is to contribute to a deeper understanding of the importance of preserving and promoting local culture. The result of this analysis is that the form of cosmetology, fashion and dance props used in each Lilin Shiva dance performance is a blend of Palembang culture which is still maintained today. The changes in the form of karya are not too obvious and can be adapted to the development of the era, both within the scope of traditional performances and in the context of contemporary dance performances.